Research and exploration of quality control indicators for nutritional therapy in critically ill patients—a multicenter before-and-after controlled study - Li, Yanhua; Wang, Youquan; Chen, Bin; Zhang, Zhe; Zhang, Dong (Frontiers in Nutrition, 2024)
Objective: To evaluate and explore the feasibility of using quality control indicators for nutritional therapy in critically ill patients as quality evaluation criteria.Methods: This study focused on critically ill patients in the intensive care unit (ICU) and conducted a cross-sectional investigation of quality control indicators for nutritional therapy in 13 hospitals in Jilin Province. The five quality control indicators including the proportion of patients receiving enteral nutrition via pump, rate of nutritional risk assessment, proportion of patients initiating enteral nutrition within 48 hours, and achievement rate of caloric and protein targets on the 7th day. After training according to the critical patients nutrition related guidelines and the latest literatures, a second cross-sectional investigation was performed. Subsequently, we conduct a comprehensive analysis of the enhancements observed in these quality control indicators both pre and posttraining, thereby assessing their viability as evaluation criteria for nutritional therapy quality in critically ill patients.Results: 1. A total of 631 patients were included before and after training, with a data acquisition rate of 97.3% for enteral nutrition pump usage and complete data collection for the remaining nutritional risk assessment rate, proportion of patients starting enteral nutrition within 48 hours, and achievement rates of caloric and protein targets on the 7th day. 2. The nutritional risk assessment rate before and after training was 88.2% vs. 94.8%, p-value is 0.003; the proportion of patients start enteral nutrition within 48 hours before and after training was 65.1% vs 75.4%, p is 0.039; and protein target achievement rate on the seventh day before and after training was 64.6% vs. 79.6%, with a p-value of 0.015，and there are significant statistical differences between the two groups.The proportion of patients with application of enteral nutrition pump before and after t training was 70.1% vs. 79.4%, p is 0.065, and the caloric target achievement rate on the seventh day before and after training was 73.4% vs. 83.9%, with a p-value of 0.062, and there was no statistical difference between the two groups.The five quality control indicators for nutritional therapy are clinically feasible and can be used as quality evaluation criteria in critically ill patients.